Diagnostic study on the relation between ozone and potential vorticity - H. Abdel Basset (Atmósfera, 2003)
A diagnostic analysis of a Mediterranean system and the associated tropopause folding for the period27 February to 10 March, 1987 is presented. Geopotential height, potential vorticity (PV ) and relativehumidity distributions were diagnosed. The analysis indicates clear correlation between the development ofthe cut-off low and the tropopause folding. A series of vertical cross-sections at the ends of the jet streaksdemonstrated that a fold could be captured using potential vorticity and relative humidity. Q-vectors wereemployed to investigate vertical motion in the vicinity of the fold and showed the exact positions of descentcorresponding to the fold along the entire length of the jet streak. The analysis also shows that the strongcorrelation between total ozone and column integrated potential vorticity holds well for all levels. As bothquantities are integrals through the atmosphere this result is consistent with, but does not prove, a highindependent linear dependence between ozone and PV . More case studies are needed to assure the highlinear dependence between ozone and PV . The maximum transport of ozone from the stratosphere to thetroposphere is coinciding with the maximum developing system, and also with the maximum values of PV .